-12+4x=7(2x+4)

Simple and best practice solution for -12+4x=7(2x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12+4x=7(2x+4) equation:


-12+4x=7(2x+4)

We simplify the equation to the form, which is simple to understand
-12+4x=7(2x+4)

Reorder the terms in parentheses
-12+4x=+(+14x+28)

Remove unnecessary parentheses
-12+4x=+14x+28

We move all terms containing x to the left and all other terms to the right.
+4x-14x=+28+12

We simplify left and right side of the equation.
-10x=+40

We divide both sides of the equation by -10 to get x.
x=-4

See similar equations:

| 3(5x-6)+7(10-x)= | | x^2+2x^2+6x^2=2x^2+4x^2 | | 3n+7(1+4n)=37+n | | 4.3q-2.8-5.8q=0.5q-2.8 | | -3(y-4y)+6=-4(2y-y)+4+12y | | 4x^2+24x^2+36x^2=4x^2+16x+16 | | 35x^7+25x^5+15x^3= | | 120/55=45.6/a | | -10-8x=7+3(x+1) | | -2=3y-18-55y | | 4x^4-75xy^3=0 | | 4x^2+25x^5+26x^4=4x^2+16x+16 | | x^2+6x-4= | | 30y^3+84y+120y^2= | | 2y^2-13y+20=0 | | 4(x)-8(x+1)=8 | | 4x-14=6(x-3) | | 13-2/9x=9 | | (x^3+x^2+2x-4)/(x-1) | | -15+x=x+20 | | x^2+24x+36=36x+81 | | 5(a-7)+10=3(a-5) | | -10x-19=19+-8x | | (1/5)-(1/4) | | 31+x=3(5+3x) | | x(x+8)=308 | | 6(5r+3)=-15-3r | | 800+16y=720+21y | | (2-3x)+(3-4x)= | | B-5+2b=26 | | 110-x+4x=180 | | 4x^6+24x^5+36x^4=4x^2+16x+16 |

Equations solver categories